1996
DOI: 10.1289/ehp.961041431
|View full text |Cite
|
Sign up to set email alerts
|

Leukemia risk associated with benzene exposure in the Pliofilm cohort.

Abstract: A reanalysis of the Pliofilm cohort was conducted incorporating six additional years of follow-up information gathered by the National Institute of Occupational Safety and Health (NIOSH) and a new set of exposure estimates developed recently. The distribution of individual worker exposures calculated with the Paustenbach exposure estimates was compared to those derived using two earlier sets of job-, plant-, and year-specific exposure estimates. A traditional standardized mortality ratio analysis and the Cox p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Interest in this cohort has remained high since the previous update. Other researchers have performed independent analyses, varying statistical analyses, and sometimes proposing the use of other exposure estimates [Paustenbach et al, 1992;Crump, 1994Crump, , 1996Paxton et al, 1994;Paxton, 1996;Finkelstein, 2000]. Regardless of which exposure estimates were used, the level of exposure to benzene has consistently shown a statistically significant relationship to leukemia mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Interest in this cohort has remained high since the previous update. Other researchers have performed independent analyses, varying statistical analyses, and sometimes proposing the use of other exposure estimates [Paustenbach et al, 1992;Crump, 1994Crump, , 1996Paxton et al, 1994;Paxton, 1996;Finkelstein, 2000]. Regardless of which exposure estimates were used, the level of exposure to benzene has consistently shown a statistically significant relationship to leukemia mortality.…”
Section: Introductionmentioning
confidence: 99%
“…When the cohort was expanded to include workers exposed to benzene for at least a day between January 1, 1940 and December 31, 1965, and followed through December 31, 1981 [Rinsky et al, 1987], there were nine deaths from leukemia versus 2.7 expected, for an SMR of 3.37 (95% CI ¼ 1.54-6.41). Using data collected by Rinsky et al for a NIOSH follow-up of these workers through 1987, Paxton [1996 published a report showing 14 leukemia deaths among male workers versus an expected number of 3.89, for an SMR of 3.60 (95% CI 1.97-6.04). Vital status of the cohort has subsequently been followed through 1996 [Rinsky et al, 2002, this issue], with 15 deaths and an SMR for leukemia of 2.56 (95% CI ¼ 1.43-4.22) observed among white males.…”
Section: Introductionmentioning
confidence: 99%
“…This 200 ppm-yr threshold dose for AML is more conservative than other estimates, because it is calculated from exposure estimates reported by Rinsky et al (1987), which are much lower than exposure estimates developed by Crump and Allen (1984) and Paustenbach et al (1992). For example, Paxton (1996) showed that there was an apparent threshold for production of AML of about 400 ppm-yr based on the Paustenbach et al (1992) exposure analysis. The acceptable lifetime dose of benzene based on current OSHA guidelines ( Table 3, PEL 1 ppm for benzene) is equivalent to 40 ppm-yr.…”
Section: Discussionmentioning
confidence: 74%
“…Some have suggested that exposure to benzene may be associated with other leukemias, such as chronic myeloid leukemia and multiple myeloma (NIOSH, 1977;Rinsky et al, 1981Rinsky et al, , 1987Snyder, 2000). However, failure to identify additional cases of multiple myeloma in the Pliofilm cohort weakens any previously reported associations between multiple myeloma and benzene exposure (Paxton et al, 1994a(Paxton et al, , 1994bPaxton, 1996;Wong, 1995). No association between leukemogenic effects and low or background concentrations of benzene (less than 0.5 ppm) has been shown (Raabe & Wong, 1996).…”
mentioning
confidence: 99%